Determinative Energy Dissipation in Liquid Metal Polymer Composites for Advanced Electronic Applications. Issue 5 (3rd March 2020) - Xin, Yumeng; Zhang, Shiliang; Lou, Yang; Xu, Jun; Zhang, Jiuyang
Abstract: Attributed by the unique mechanical and electrical properties, functional blends of liquid metals (LMs) and polymers have received lots of attention. The deformation of LM‐polymer materials under extreme force to create electrical conductivity has built many electronic applications. However, the fundamental understanding of the relationship among polymer networks, LM deformation, and electrical conductivity remains too opaque to have a general principle for further advanced LM‐polymer electronics. This work discovered that the energy dissipation of polymer matrix plays a determinative role in controlling the electrical behaviors of LM‐polymers. The relationship among polymer network, deformation, and external pressure is investigated to design many unique electronic applications not shown in prevalent LM elastomers. The human pressure successfully disrupts high energy dissipated (HED) polymer networks and cracks LM fillers to provide anisotropic conductivity along pressure direction while insulated in planar directions. Meanwhile, under flexural forces, the HED LM‐polymer film can be also conductive along the maximum curvature of films but insulated in intact areas. Different folded and printed circuits are customized and prepared from the HED LM‐polymers. In addition, a new generation of anisotropic electrical adhesives is successfully fabricated from HED LM‐polymer resins, which shows advantages over current commercially available products. Abstract : This work discovered that the energy dissipation of polymer matrix plays a determinative role in controlling the electrical behaviors of liquid metal polymer composites. External forces can successfully induce the electrical conductivity in high energy dissipated polymer matrix with the conductive direction and pattern precisely determined by the forces.